2020
DOI: 10.23917/forgeo.v34i1.10862
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Land Surface Temperature During and Before the Emergence of Covid-19 using Modis Imagery in Wuhan City, China

Abstract: Coronavirus disease (COVID-19) was firstly identified in Wuhan, China. By 23rd January 2020, China’s Government made a decision to execute lockdown policy in Wuhan due to the rapid transmission of COVID-19. It is essential to investigate the land surface temperature (LST) dynamics due to changes in level of anthropogenic activities. Therefore, this study aims (1) to investigate mean LST differences between during, i.e., December 2019 to early March 2020, and before the emergence of COVID-19 in Wuhan; (2) to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 17 publications
3
30
0
1
Order By: Relevance
“…Signify the LST results of Hadibasyir et al [11] research, this result found the similar phenomena in Wuhan China, although they used different resolution of satellite imagery. During the lock down policy both areas, Wuhan and Jakarta, experienced the same phenomena.…”
Section: Correlation Of Uhi and Covid-19 Casessupporting
confidence: 71%
See 1 more Smart Citation
“…Signify the LST results of Hadibasyir et al [11] research, this result found the similar phenomena in Wuhan China, although they used different resolution of satellite imagery. During the lock down policy both areas, Wuhan and Jakarta, experienced the same phenomena.…”
Section: Correlation Of Uhi and Covid-19 Casessupporting
confidence: 71%
“…This study uses surface UHI as a parameter to determine UHI so that image data for obtaining LST values is carried out using LANDSAT-8. Several studies of the same study have also been carried out, such as Hadibasyir et al [11] showing that the average LST value in built-up areas experienced a significant difference in the form of a decrease in the LST value of 1.19 0 C. Research in the United Arab Emirates on the implementation of lockdown was able to reduce the value of the surface urban heat island intensity (SUHII) by 19.2% [12].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that identifying land surface temperature contributes to better urban planning and partially prevents increases in temperatures and the urban heat island phenomenon in urban areas. This observation was also made previously by [23,34].…”
Section: Resultssupporting
confidence: 87%
“…Reference [22] reported an overall decrease in LST values in Dehradun City, India, during the post-COVID lockdown time. Another research conducted in Wuhan City, China, by [23] reveals that during the COVID-19, the mean LST was lower than the mean LST of the last three years on the same dates. Meanwhile, during the emergence of COVID-19 without a lockdown strategy, the mean LST was comparatively higher than the mean LST of the last three years.…”
Section: Introductionmentioning
confidence: 92%
“…The UHI variations during lockdown periods were evaluated as the differences in the mean UHII between the COVID-19 breakout year (i.e., 2020) and the reference period (i.e., 2017-2019). Here, a reference period of 3 years was selected to reduce biases caused by interannual UHI variations (Hadibasyir et al, 2020). Further discussion on possible uncertainties related to the reference period is provided in Text S3 in Supporting Information S1.…”
Section: Analysis Of Uhi Variations During Covid-19 Lockdownmentioning
confidence: 99%